Riyad-us-Saliheen: (Vol.2) - Al-Nawawi, Abu Zakariyyah Yahya bin Sharaf, Ad-Dimashqi; Commentry bySalahuddin Yusuf: Transl. by Amin Muhammad and Revised by Murad, M.R. (Lahore Darussalam, 1999)
The book was compiled by Imam An-Nawawi who was the great scholar of Hadith and Fiqhof his time. Commentaries on the Ahadith have been added by Hafiz Salahuddin Yusuf of Pakistan who had originally executed them for the Urdu edition of this book. The English translation of the book and the - commentaries was performed by Dr. Muhammad Amin and Abu Usamah Al-Arabi bin Razduq who have performed their task with utmost care and profound interest.
Keywords: Hadith